1981
DOI: 10.1007/bf00844270
|View full text |Cite
|
Sign up to set email alerts
|

A method to increase compliance to exercise regimens in rheumatoid arthritis patients

Abstract: A hand exerciser with an electronic counter and a visual display was used to measure compliance objectively, to investigate the effects of visual feedback on compliance, and to assess the impact of exercise on seven mild and five moderate rheumatoid arthritis patients. A multiple time-series design varying the onset of the visual display was utilized. Compliance was assessed weekly over the 7 weeks of the study. Pretest and posttest measures of various indicators of hand functioning were taken by an occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…This approach is consistent with recent practice [43]. The year 1981 was chosen as the starting point for study searches based on a preliminary search in PubMed in which the first cited randomized controlled trial on exercise and arthritis in adults was published in 1981 [44]. …”
Section: Methodsmentioning
confidence: 99%
“…This approach is consistent with recent practice [43]. The year 1981 was chosen as the starting point for study searches based on a preliminary search in PubMed in which the first cited randomized controlled trial on exercise and arthritis in adults was published in 1981 [44]. …”
Section: Methodsmentioning
confidence: 99%
“…All studies measured 1 or 2 of the following process measures: compliance (16,59), grip strength (42,56 -58,60), and range of motion (16,42,56 -58,60). In the high quality RCT (42), no significant differences in grip strength between groups were found, whereas in the low quality RCT (56), significant changes in grip strength after training of hand function were reported.…”
Section: Steultjens Et Almentioning
confidence: 99%
“…Only two studies of these interventions have been performed with RA patients. Waggoner and LeLieuvre [44] developed and tested a behavioral approach to improve adherence with a hand exercise regimen. It was found that adding an automated electronic counter with a visual display to a hand exercise device improved mean adherence among 1 2 patients from 83% to 97%.…”
Section: Interventions For Enhancing Adherencementioning
confidence: 99%
“…These measures ideally should encompass both the frequency and the qualitative aspects of home exercise and the cognitive-behavioral treatments. Further development of automated exercise recording devices such as that produced by Waggoner and LeLieuvre [44] is encouraged. However, it might also be useful to devote effort to evaluating the reliability and validity of family members' unobtrusive recordings of patient behavior.…”
Section: Summary Am) Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation